2014
DOI: 10.1007/s12602-014-9174-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Monocytes by Probiotic and Selected Lactic Acid Bacteria

Abstract: Some lactic acid bacteria (LAB), especially bacteria belonging to the genus Lactobacillus, are recognized as common inhabitants of the human gastrointestinal tract and have received considerable attention in the last decades due to their postulated health-promoting effects. LAB and probiotic bacteria can modulate the host immune response. However, much is unknown about the mediators and mechanisms responsible for their immunological effect. Here, we present a study using cytokine secretion from the monocytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Based on previous work, we suggest that there is poor communication between LAB, probiotics, and immune cells; we also speculate that pro- and anti-inflammatory mediators are regulated by probiotics and have potential roles in the immune response [26, 27]. Bacterial surface proteins, metabolites, and secreted proteins can stimulate cytokine secretion and can activate NF-κB in cells in vitro [28]. However, the effects of these bacterial products on host cytokine secretion and its blood level require in vivo support and exploration to be better understood; our study employs a mixture of bacteria at various concentrations, and laboratory rats as the experimental in vivo components, to address this.…”
Section: Introductionmentioning
confidence: 94%
“…Based on previous work, we suggest that there is poor communication between LAB, probiotics, and immune cells; we also speculate that pro- and anti-inflammatory mediators are regulated by probiotics and have potential roles in the immune response [26, 27]. Bacterial surface proteins, metabolites, and secreted proteins can stimulate cytokine secretion and can activate NF-κB in cells in vitro [28]. However, the effects of these bacterial products on host cytokine secretion and its blood level require in vivo support and exploration to be better understood; our study employs a mixture of bacteria at various concentrations, and laboratory rats as the experimental in vivo components, to address this.…”
Section: Introductionmentioning
confidence: 94%
“…In this context, the immunomodulatory effects of probiotic Lactobacillus strains have also been shown to decrease the inflammatory response under some pathological conditions such as necrotizing enterocolitis and allergies in children [6, 7]. In other in vitro studies, some strains produced an increase in the production of proinflammatory cytokines such as TNF- α , IL-12, and IL-8 whereas others produced increases in the secretion of anti-inflammatory cytokines such as IL-10 [8, 9]. A study by Lopez et al [10] showed that UV-inactivated and live Lactobacillus rhamnosus GG (LGG) are equally effective in decreasing IL-8 in the intestinal epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…are well‐known probiotics. Lactobacilli are claimed to provide a number of health benefits including anti‐tumour effects (Dasari et al ., ), anti‐cholesterol effects (Tulumoglu et al ., ), immuno‐modulation (Jensen et al ., ), treatment of diarrhoea (Mantegazza et al ., ) and antimicrobial effects against pathogens (Tulumoglu et al ., ). Consuming probiotics is not the only way to re‐establish balance of human health.…”
Section: Introductionmentioning
confidence: 99%